Successful treatment with dupilumab for mucus plugs in severe asthma. Issue 1 (15th December 2022) - Anai, Moriyasu; Yoshida, Chieko; Izumi, Hiroki; Muramoto, Kei; Saruwatari, Koichi; Tomita, Yusuke; Ichiyasu, Hidenori; Sakagami, Takuro
Abstract: A 29‐year‐old man presented to our hospital with severe eosinophilic asthma. He needed a short OCS burst for exacerbation of asthma once every 1 or 2 months, although he used a high dose of inhaled corticosteroids and a long‐acting beta‐2 agonists. Chest CT showed multiple mucous plugs with bronchiectasis, but further examination found that he did not meet the diagnostic criteria for allergic bronchopulmonary aspergillosis. After starting dupilumab for his severe eosinophilic asthma, his asthma control improved without exacerbation. Furthermore, most mucus plugs disappeared on chest CT after 16 weeks from initiating dupilumab. This case suggests that dupilumab may be an effective treatment against mucus plugs associated with severe eosinophilic asthma. Abstract : We report a case of severe asthma in which the introduction of dupilumab improved the mucus plugs in addition to asthma control.